Dysmenorhore Exercises Reduce Menstrual Pain in Teenagers: DYSMENORRHEA EXERCISES TO REDUCE MENSTRUAL PAIN IN ADOLESCENTS - Erni Chaerani; Hendra Kusumajaya; Nurwijaya Fitri (STIKes Maharani Malang, 2025)
Dysmenorrhea or unpleasant menstruation is the most common gynecological problem among young women, including lower abdominal pain, nausea and mild headaches. Dysmenorrhea exercise is a relaxation method that can be used to reduce discomfort (pain) during menstruation. This study aims to determine the effect of dysmenorrhoea exercises in reducing menstrual pain on the Pangkalpinang Ministry of Health Polytechnic students. The research design used was pre-experimental single group pretest-post test design with a research sample of 91 people. The results showed that the average pain level of respondents before doing dysmenorrhea exercises was 6,13 with a standard deviation of 1,784, while after doing dysmenorrhea exercises, the average pain level of respondents was 3,95 with a standard deviation of 1,797. The statistical test results obtained a p value of 0,000, it was concluded that there was a significant influence on the respondent's pain level before and after doing the dysmenorrhoea exercise. This means that dysmenorrhoea exercise has an influence in reducing the respondent's menstrual pain. It is hoped that the results of this research will provide benefits to educational institutions as reference material in learning, and for the community, especially teenagers, to avoid the symptoms of endometriosis which have an impact on women's health, quality of life and fertility.